Ribosomal protein gene cluster analysis in eubacterium genomics: homology between Sinorhizobium meliloti strain 1021 and Bacillus subtilis - Barloy-Hubler, Frédérique (Oxford University Press, 2001)
The first whole genome sequence of a symbiotic soil bacterium, Sinorhizobium meliloti (formely named Rhizobium meliloti) strain 1021, is due in 2001. As an active participant in the European and North American consortium that has completed this work, our group has sequenced a region on the chromosome containing clusters rpoBC, str, S10, spc and alpha corresponding to 30 protein genes. The structural organization and function of these genes were compared with those of orthologs in another 15 complete eubacterial genomes available in databases. This study, involving the DNA and amino acid sequences as well as the organization of the whole region (gene order, cluster order, etc.), has shown that the phylogenetic tree resulting from a comparison of the amino acid sequence is rather similar to that derived from 16S rRNA sequence data. However, the tree achieved by aligning DNA sequences groups the organisms with a high GC content (>60% GC), while that based on a comparison of gene cluster orientation and organization reveals a greater level of correspondence between the α-proteobacteria S.meliloti and the firmicute Bacillus subtilis.